The Different Moral Bases of Patient and Surrogate Decision-Making - Brudney, Daniel (The Hastings Center report, 2018)
My topic is a problem with our practice of surrogate decision-making in health care, namely, the problem of the surrogate who is not doing her job—the surrogate who cannot be reached or the surrogate who seems to refuse to understand or to be unable to understand the clinical situation. The analysis raises a question about the surrogate who simply disagrees with the medical team. One might think that such a surrogate is doing her job—the team just doesn't like how she is doing it. My analysis raises the question of whether (or perhaps when) she should be overridden. In approaching this problem, I focus not on the range of difficulties in practice but on the underlying moral conceptual issue. My concern will be to show that the moral values that underpin patient decision-making are fundamentally different from those that underpin surrogate decision-making. Identifying the distinctions will set parameters for any successful solution to the “Who should decide?” question. A patient has a specific kind of moral right to make her own medical decisions. A surrogate has no analogous moral right to decide for someone else. We want the surrogate to make the decision because we believe that she has a relevant epistemological advantage over anyone else on the scene. If and when she has no such advantage or if she refuses or is unable to use it, then there might not be sufficient reason to let her be the decision-maker.